PENGARUH LAYANAN DAN KOMITMEN TERHADAP KEPERCAYAAN MASYARAKAT MELALUI KEPUASAN MASYARAKAT DI LAPORGUB JAWA TENGAH - Mehilda Putri; Mahfudz Mahfudz (Jurnal Akuntansi dan Pajak, 2023)
This research takes the object of study on the Central Java LaporGub Application, which is an application with the aim of providing public services regarding community complaints and being able to help resolve conflicts faced by the community. The research objective was to analyze and test the effect of service quality, commitment to public trust through community satisfaction in LaporGub Central Java. The research sample was determined as many as 160 respondents using a purposive sampling technique, namely a sampling technique with criteria or considerations, including: people who use LaporGub services, at least 17 years old and willing to be respondents. The direct test results found that service has a positive effect on community satisfaction, commitment has a positive effect on community satisfaction, service has a positive effect on public trust, commitment has a positive effect on public trust and community satisfaction has a positive effect on public trust. The results of this study can be followed up with studies to other parties related to the Central Java Laporgub application, such as employees within the Governor of Central Java and other parties who have an interest in the Central Java Laporgub application. Keywords: service, commitment, satisfaction, and public trust